Slovak Ethnology in the Post-Socialist Era - Scheffel, David (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1999)
The article examines developments in Slovak ethnology following the collapse of communism and Slovakia’s declaration of independence. Despite its small size and the erosion of state subsidies, the discipline has managed to sustain two periodicals and an impressive output of publications. While the traditional emphasis on Slovak folk culture continues, interest in anthropological and sociological topics is on the rise among the younger generation. Ethnic relations, especially pertaining to the “Magyar question”, is a particularly popular contemporary research theme.